2009
DOI: 10.1556/aagr.57.2009.1.7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of liquid and cyst formulations of Azospirillum with inorganic nitrogen on the growth and yield of rice

Abstract: The nitrogen-fixing rhizobacterium Azospirillum lives in close association with plant roots, where it exerts beneficial effects on the plant growth and yield of many crops of agronomic importance. As carrier-based inoculants have a short shelf life and poor quality, new liquid and cyst formulations of inoculants have been developed and standardized for Azospirillum. In the present investigation, experiments were conducted to study the effect of liquid and cyst formulations of Azospirillum, combined with inorga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Thamizh Vendan and Thangaraju (2007) inoculated the tomato seeds with liquid formulation of Azospirillum which enhanced the plant height, biomass, nitrogen uptake of plants, available nitrogen content of soil and yield of tomato. Kavitha (2011) reported that rice ADT 43 seeds bioprimed with liquid Azospirillum 20% for 12h expressed high values for speed of germination and vigour based on dry matter production accounted for 32 and 7 per cent increase over nonprimed seed.…”
Section: Resultsmentioning
confidence: 99%
“…Thamizh Vendan and Thangaraju (2007) inoculated the tomato seeds with liquid formulation of Azospirillum which enhanced the plant height, biomass, nitrogen uptake of plants, available nitrogen content of soil and yield of tomato. Kavitha (2011) reported that rice ADT 43 seeds bioprimed with liquid Azospirillum 20% for 12h expressed high values for speed of germination and vigour based on dry matter production accounted for 32 and 7 per cent increase over nonprimed seed.…”
Section: Resultsmentioning
confidence: 99%